صيغ و أساليب التمويل الإسلامي للمؤسسات الإقتصادية في ظل قانون الصيفة الإسلامي الجديد02/20 -دراسة حالة بنك البركة - - عبد الله عوادية; خليل قواسمية (My University, 2022)
The Islamic economy has methods and financing formulas that push it to achieve development and prosperity. Through our study of the subject of Islamic financing formulas and methods according to the modern banking system, we came to the following: Results. Through this study, the following results were reached: 1- Banking and financial transactions in Islam are governed by principles and provisions that must be observed when applying these transactions. 2- Islamic financing formulas are diverse and numerous and are characterized by the high flexibility that makes them meet various financing desires. 3- Islamic banks have achieved great success through practicing their various activities and services in accordance with the provisions of Islamic Sharia, and the most important of these services are: financial services. 4- Al-Baraka Bank of Algeria is considered one of these banks that has spread all over the world. It practices various banking activities, especially the financing activity, in accordance with the provisions of Islamic Sharia. Recommendations: Through this study, we reached some recommendations, including: 1- That such topics be adopted by scholars who have experience in transactions from a jurisprudential point of view, to ensure their legitimacy. 2- Islamic banks should devise scientific methods in choosing their clients according to their new investment methods. Caution in its investment activity based on participation in the return on investment, in order to be able to expand this activity, and then it can contribute positively to the performance of the expected economic role. 3- Increasing the role of Islamic banks in the foreign trade shops of the Islamic world in the field of export and import. 4- Cooperation between Islamic banks in order to establish joint investment projects on the scale of Islamic countries because of its impact on achieving economic integration among these countries, and what it achieves in confronting the Western multinational companies that invade the Islamic world at the present time in order to achieve their economic interests in particular. Regardless of the interests of the Islamic world. ............................................................. يتوفر ا لاقتصاد ا لاسلامي على أ ساليب و صيغ تمويلية تدفعه الى تحقيق التنمية و ا لازهار ومن خلال دراستنا لموضوع صيغ و اساليب التمويل ا لاسلامي وفق نظام الصيرفة الحديث توصلنا الى : نتائج الدراسة. تم التوصل من خلال هذه الدراسة إلى النتائج التالية: 1 -تحكم المعاملات المصرفية والمالية في الإسلام مبادئ وأحكام يجب مراعا ا عند تطبيق هذه المعاملات. 2 -صيغ التمويل الإسلامي متنوعة ومتعددة وتتميز بالمرونة العالية التي تجعلها تلبي ثتلف الرغبات التمويلية. 3 -المصةارف الإسةلامية حققت نجاحا واسةعا من خلال ممارسةتها لأنشةطتها وخدما ا المختلفة طبقا لأحكام الشةريعة الإسلامية، ومن أهم هذه الخدمات: الخدمات التمويلية. 4 -بنك البركة الجزائري يعتبر أحد هذه المصةارف التي انتشةرت في جميع أنحاء العالم، فهو يمار ثتلف الأنشةطة المصرفية، وعلى رأسها النشاط التمويلي، وذلك طبقا لأحكام الشريعة الإسلامية. توصيات: من خلال هذه الدراسة توصلنا إلى بعض التوصيات نذكر منها 1 - أن يتب مثل هذه المواضةيع علماء لهم خبرة في المعاملات من الناحية الفقهية للتأكد من مشةروعيتها. 2 - على المصةارف الإسةلامية اسةتنباط المناهج العلمية في اختيار المتعاملين معها وفقا لأسةاليبها الاسةتثمارية الجديدة، وفي هذا الصدد يمكن تشجيع جيل جديد من المستثمرين الذين يرغبون في التعامل وفق الأساليب الإسلامية في الاستثمار على أن تضةع المصةارف ضةمن أهدافها التوصةل إلى أسةاليب قانونية وتشةغيلية تسةاعد على أحد جانب الحيطة والحذر في نشةاطها الاسةتثماري القائم على المشةاركة في عائد الاسةتثمار، وذلك كي تتمكن من التوسةع في هذا النشةاط، ومن ثم يمكن أن تسةاهم إيجابيا في أداء الدور الاقتصةادي المنتظر منها. 3 - زيادة دور المصةارف الإسةلامية في محال التجارة الخارجية لدول العالم الإسةلامي في مجال التصةدير والاسةتيراد. 4 - التعاون بين المصةارف الإسةلامية لأجل إنشةاء المشةروعات الاسةتثمارية المشةتركة على نطاق الدول الإسةلامية لما لذلك من أثر في تحقيق التكامل الاقتصةادي بين هذه الدول، ولما يحققه من مواجهة للشةركات الدولية الغربية متعددة الجنسةية التي تغزو العالم الإسةلامي في وقتنا الحاضةر لأحل تحقيق مصالحها الاقتصادية بصفة خاصة، بصرف النظر عن مصالح العالم الإسلامي